Analysis of Energy Saving Potential Through Rooftop PV System Implementation at Atria Hotel, Magelang City - Hayati, Nur; S, Arbye; Aziizudin, Achmad; -, Diyono; Ceren, Tiko Es Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
The growing energy demand in the hospitality sector highlights the urgent need for efficient and environmentally friendly renewable energy sources. This study investigates the potential for energy savings in hotel buildings through the implementation of rooftop photovoltaic (PV) systems in Magelang City, with a case study at Atria Hotel. The methodology involved analyzing secondary data on solar energy potential, estimating available rooftop area, simulating PV system capacity, and evaluating energy production and economic savings based on the hotel’s laundry energy requirements. The results indicate that Magelang has substantial solar energy potential, with an average Global Horizontal Irradiance (GHI) exceeding 4.8 kWh/m²/day. At Atria Hotel, a rooftop PV system with a capacity of 4.58 kWp can generate approximately 6,656 kWh of electricity annually, meeting around 25% of the laundry facility’s electricity demand. This implementation translates into annual electricity cost savings of IDR 2,635,136.73. These findings demonstrate that rooftop PV systems represent a strategic solution for enhancing energy efficiency and advancing sustainable hotel development in Magelang City.